(untitled) (Journal of Contemporary Educational Policies and Practices, 2025)
In the context of increasing technology integration in higher education, understanding how students’ attitudes toward technology relate to learning outcomes has become an essential line of inquiry. This cross-sectional study tests a structural mediation model (H1-H5) examining how four technology attitudes - Positive Attitude, Anxiety, Negative Attitude, and Task Switching - affect Academic Performance through Academic Engagement. Data were collected from 679 pharmacy students in Vietnam using a validated self-report questionnaire. Measurement models were examined through Exploratory and Confirmatory Factor Analyses (EFA/CFA), and hypotheses were tested using Structural Equation Modeling (SEM). The Confirmatory Factor Analysis confirmed the 15-item Media and Technology Usage and Attitude Scale (MTUAS) (RMSEA = 0.067) but indicated poor fit for the 3-factor Utrecht Work Engagement Scale for Students (UWES-9S) (RMSEA = 0.110), justifying the use of a composite engagement score. Structural model results suggested that the path from Academic Engagement to Academic Performance (H5) was not statistically significant (p = 0.073), leading to the rejection of all four indirect-mediation hypotheses (H1-H4). These findings do not support the proposed mediation framework and provide empirical evidence for the “engagement-achievement paradox,” suggesting that, in this Vietnamese pharmacy cohort, technology attitudes and self-reported engagement may not directly translate into measurable academic performance outcomes.